VISIBILITY OF THE BANYUMAS DIALECT IN THE ACADEMIC ENVIRONMENT AS A MINORITIZED LANGUAGE: A LINGUISTIC LANDSCAPE STUDY - Yulian Purnama; Linda Ayu Darmurtika; I Made Sutama; Putu Dewi Merlyna Yuda Pramesti; Kadek Wirahyuni (Technopreneurship and Educational Development Review (TENDER), 2026)
Research on minority languages in linguistic landscapes has predominantly focused on languages that are taxonomically distinct from the state language. However, Gorter, Cenoz, and Marten criticize this narrow approach and propose that the concept of "minority" should be expanded to include socially minoritized positions. This study applies this critique to the Banyumas dialect, a variety of Javanese that is sociolinguistically subordinate to the standard Surakarta-Yogyakarta dialect, particularly in educational settings. Using a quantitative survey documentation method, this study analyzes 100 signs in the academic environment of Banyumas Regency, covering 25 elementary schools, 25 junior high schools, 25 senior high schools, and 25 universities. The results show that the Banyumas dialect appears on 24 out of 100 signs (24%), with the highest visibility in senior high schools (36%) and the lowest in universities (12%). Based on six-level visibility continuum of Gorter, the Banyumas dialect in the academic environment is positioned at Level 4 to 5 (limited to neglected). The novelty of this research lies in its application of the minoritized language framework to a dialect—rather than a distinct language—in the Indonesian educational context. This study recommends the integration of the Banyumas dialect into the school curriculum and its strategic revitalization, with special attention to universities which have the lowest visibility.